If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2Y + 15 = 0 Reorder the terms: 15 + 2Y = 0 Solving 15 + 2Y = 0 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 2Y = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 2Y = 0 + -15 2Y = 0 + -15 Combine like terms: 0 + -15 = -15 2Y = -15 Divide each side by '2'. Y = -7.5 Simplifying Y = -7.5
| x(4-2(2.5-x+3x))= | | 3(4x+2)=-42 | | -5x+13=-22 | | -x-6=-15 | | 12x^2+11x+c=0 | | 5x+4=2(3x-2) | | 4x-6y=6 | | -5x+5y=5 | | 10+5(z-2)=4z+1 | | 4x^4-16x^2+8x+5=0 | | 9x^2-37x+4=0 | | x^2-4x+32=0 | | 5a-3=12 | | ln(x^2+1)=60 | | 4x=140 | | 4x=139 | | -4+12=16x-3-15x | | 2a-24=a+12 | | 17x-4=12x+8 | | 15x^4-19x^2+6=0 | | 17x-4=12x+B | | 2a-12=a+12 | | -5c+1=-24 | | 2a+12=a+12 | | 3q^2-5q-6q^2+3q= | | 3x+17=21-5x | | 0.07x+x=6981.61 | | 0.7x+x=6981.61 | | 12x^3+2x^2-3x=0 | | 0.2x=7 | | 3(z-5)=2z | | 2t-9=3(t+4) |